The Asymptotic Behaviours of a Class of Neutral Delay Fractional-Order Pantograph Differential Equations - Baojun Miao; Xuechen Li (Advances in Mathematical Physics)
By using fractional calculus and the summation by parts formula in this paper, the asymptotic behaviours of solutions of nonlinear neutral fractional delay pantograph equations with continuous arguments are investigated. The asymptotic estimates of solutions for the equation are obtained, which may imply asymptotic stability of solutions. In the end, a particular case is provided to illustrate the main result and the speed of the convergence of the obtained solutions.